OP0119 Great progress but much more needed: Hospitalizations due to complicated gastric and duodenal ulcers in the US (1990-2009). (23rd January 2014) - Singh, G.; Mannalithara, A.; Mithal, A.; Triadafilopoulos, G.
Abstract : Background: Gastrointestinal bleeding, perforation, and obstruction of gastric (GU) and duodenal ulcers (DU) (collectively Peptic Ulcer Disease, PUD) are significant causes of hospitalizations and mortality in the US. Objectives: To examine hospitalizations due to complicated GUs and DUs over 20 years and correlate them to introduction of anti- H pylori eradication strategies and changes in the use of NSAIDs and COX-2 specific inhibitors in the US. Methods: The Nationwide Inpatient Sample (NIS) is a stratified random sample of US community hospitals, with detailed information on all hospitalizations, regardless of payer 1 . We studied hospitalizations from 1990-2009 with a primary diagnosis of complicated ulcers (GU, DU, PUD) and analyzed them as a proportion of total all-cause hospitalizations. Results: From 1990 to 2009 there were 732.2 million hospitalizations in the US. Of these, 2.8 million (0.38%) were for a complicated GU, DU, or PUD. All-cause hospitalizations increased from 34.9 million in 1990 to 39.4 million in 2009, probably reflecting the growth of the aging population. However, hospitalizations for complicated GU, DU and PUD declined from 163, 544 in 1990 to 100, 589 in 2009 (see Figure). The decline started in 1995, following the NIH consensus conference in 1994 recommending H. pylori eradication and continued through the introduction of coxibs in 1999, and then the withdrawal of 2 coxibs in 2004-5. Complicated PUD hospitalizations transiently increased in 2005, but then resumed their steady decline in recent years even as Cox-2 specific inhibitor prescriptions continued to decrease. Conclusions: National population data strongly suggest that the introduction of H. pylori eradication therapy triggered a trend towards fewer hospitalizations for complicated ulcer disease in the US. The continuing decline in hospitalizations may reflect better physician and patient education and increasing use of gastroprotective therapies. Nevertheless, the number of PUD hospitalizations in 2009 still remains disturbingly high (>100, 000) and calls for continuous education on safer NSAID prescribing, gastroprotection and vigilance. References: [1] HCUP Nationwide Inpatient Sample (NIS). Healthcare Cost and Utilization Project (HCUP). 2007-2009. Agency for Healthcare Research and Quality, Rockville, MD. www.hcup-us.ahrq.gov/nisoverview.jsp Disclosure of Interest: G. Singh Grant/Research support from: Horizon Pharma, Pfizer, Astra-Zeneca, Pozen, Sunovion, Consultant for: Pfizer (no personal compensation), A. Mannalithara: None Declared, A. Mithal: None Declared, G. Triadafilopoulos: None Declared